Birth outcomes affecting infants of mothers with intellectual and developmental disabilities. Issue 6 (6th May 2021) - Rubenstein, Eric; Ehrenthal, Deborah B.; Mallinson, David C.; Bishop, Lauren; Kuo, Hsiang‐Hui; Durkin, Maureen S.
Abstract: Background: Women with intellectual and developmental disabilities (IDD) face increased risk of adverse maternal pregnancy outcomes, yet less is known about infant outcomes. Objectives: To examine birth outcomes of infants born to mothers with IDD and assess associations with demographics and IDD‐type. Methods: We used data from the Big Data for Little Kids project, which links Wisconsin birth records to Medicaid claims for live births covered by Medicaid from 2007 to 2016. We identified IDD using maternal prepregnancy Medicaid claims and ran Poisson regression (with a log link function) with robust variance clustered by mother to compare prevalence of outcomes between singleton births with and without mothers with IDD. We adjusted the associations for demographic factors and estimated prevalence ratios (PR) as the effect measure. We assessed outcomes by IDD‐type (intellectual disability, genetic conditions, cerebral palsy, and autism spectrum disorder) to explore differences by categories of IDD. Results: Of 267, 395 infants, 1696 (0.6%) had mothers with IDD. A greater percentage of infants with mothers with IDD were born preterm (12.8% vs 7.8%; PR 1.64, 95% confidence interval [CI] 1.42, 1.89), small for gestational age (8.5% vs 5.4%; PR 1.42, 95% CI 1.25, 1.61), and died within 12 months of birth (3.2% vs 0.7%; PR 4.93, 95% CI 3.73, 6.43) compared to infants of mothers without IDD. Prevalence ratios were robust to adjustment for demographics factors. Estimates did not meaningfully differ when comparing different IDD‐types. Conclusions: A greater porportion of infants born to mothers with IDD who were covered by Medicaid had poor outcomes compared to other infants. Prevalence of poor infant outcomes was greater for mothers with IDD even after accounting for demographic differences. It is imperative to understand why infants of mothers with IDD are at greater risk so interventions and management can be developed.